2008
DOI: 10.1021/bp049780w
|View full text |Cite
|
Sign up to set email alerts
|

On the Optimal Ratio of Heavy to Light Chain Genes for Efficient Recombinant Antibody Production by CHO Cells

Abstract: Monoclonal antibodies (Mab) are heterotetramers consisting of an equimolar ratio of heavy chain (HC) and light chain (LC) polypeptides. Accordingly, most recombinant Mab expression systems utilize an equimolar ratio of heavy chain (hc) to light chain (lc) genes encoded on either one or two plasmids. However, there is no evidence to suggest that this gene ratio is optimal for stable or transient production of recombinant Mab. In this study we have determined the optimal ratio of hc:lc genes for production of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
167
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(192 citation statements)
references
References 61 publications
13
167
1
Order By: Relevance
“…We determined the expression at protein level of the recombinant immunoglobulin chains and found that the LC polypeptide was more abundant than the HC polypeptide (HC:LC ratio \1). This finding is consistent with previous reports suggesting that HC levels could limit productivity while LC excess is required for efficient antibody folding and assembly (Smales et al 2004;Schlatter et al 2005;Dorai et al 2006). During folding and assembly of IgG in the endoplasmic reticulum of mammalian cells, immunoglobulin chain polypeptides sequentially interact with a range of molecular chaperones, foldases, and oxidoreductases present in macromolecular complexes in the endoplasmic reticulum such as BiP (immunoglobulin binding protein) and PDI (protein disulfide isomerase) .…”
Section: Discussionsupporting
confidence: 92%
“…We determined the expression at protein level of the recombinant immunoglobulin chains and found that the LC polypeptide was more abundant than the HC polypeptide (HC:LC ratio \1). This finding is consistent with previous reports suggesting that HC levels could limit productivity while LC excess is required for efficient antibody folding and assembly (Smales et al 2004;Schlatter et al 2005;Dorai et al 2006). During folding and assembly of IgG in the endoplasmic reticulum of mammalian cells, immunoglobulin chain polypeptides sequentially interact with a range of molecular chaperones, foldases, and oxidoreductases present in macromolecular complexes in the endoplasmic reticulum such as BiP (immunoglobulin binding protein) and PDI (protein disulfide isomerase) .…”
Section: Discussionsupporting
confidence: 92%
“…In the absence of the WPRE, the light to heavy chain mRNA ratio was nearly 1:1 at 31°C, while this ratio in the presence of the WPRE was about 5:1. It has previously been shown that the level of the light chain polypeptide is limiting for antibody assembly (35,36). Thus, the effect of the WPRE may be to increase the steady-state level of the light chain mRNA, resulting in higher light chain protein levels and higher antibody secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to increase overall productivity of these cell lines, a number of investigations have been undertaken in the past several years. These investigations, which follow closely those published in the literature, include 1) determining the optimal copy numbers of H-ch and L-ch of the therapeutic Ab in the transfectomas [17,40]; 2) utility of apoptotic resistant host cell lines [13,23,24]; 3) increased secretion of Abs via over-expression of chaperones [3] (unpublished observation); 4) prolongation of the G1 phase where protein synthesis is particularly more efficient [25] and 5) judicious use of expression systems and cell line selection strategies [2,41,42]. Recently, the "omics" approach for The effect of four different media components on multiple cell culture parameters.…”
Section: Discussionmentioning
confidence: 70%